2005
DOI: 10.1021/jp045284e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Functions of Mo/Ni/MgO in the Synthesis of Thin Carbon Nanotubes

Abstract: The functions and structures of Mo/Ni/MgO catalysts in the synthesis of carbon nanotubes (CNTs) have been investigated by transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. Thin 2-5-walled CNTs with high purities (over 90%) have been successfully synthesized by catalytic decomposition of CH(4) over Mo/Ni/MgO catalysts at 1073 K. It has been found that the yield of CNTs as well as the outer diameter or thickness correlates well with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 41 publications
4
38
0
Order By: Relevance
“…41-1487) [38], indicating that the carbon fibers were highly graphitic. The peaks at 43.8/44.4, 50.96/51.6 and 76.4/ 77.0 were the diffraction of metallic Ni° [22,37]. This observation demonstrated that the metallic nickel was the active site for the growth of carbon tubes/fibers.…”
Section: Characterization Of the Carbon Productsmentioning
confidence: 79%
See 1 more Smart Citation
“…41-1487) [38], indicating that the carbon fibers were highly graphitic. The peaks at 43.8/44.4, 50.96/51.6 and 76.4/ 77.0 were the diffraction of metallic Ni° [22,37]. This observation demonstrated that the metallic nickel was the active site for the growth of carbon tubes/fibers.…”
Section: Characterization Of the Carbon Productsmentioning
confidence: 79%
“…Catalyst coatings have been deposited by spin coating [14], dip coating [15], sputtering [16] and sol-gel techniques [17]. The catalysts are usually possessed of the element of Fe, Co or Ni [18][19][20][21][22][23]. Whereas few papers about the growth of CNTs and CNFs on metal mesh using methane as a carbon source are encountered in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make them one of the most promising candidates for bulk applications such as CNT-polymer composites, CNT film, and CNT field emission. There has been a recent flurry of interest by several researchers to synthesize tMWCNTs by catalytic chemical vapor deposition (CCVD) [1,[4][5][6]. In the previous catalyst fabrication methods for t-MWCNT synthesis, a combustion process has commonly been used to obtain Fe-Mo/MgO, [1,4] Ni-Mo/MgO [5] or Co-Mo/MgO [6] catalyst materials.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a recent flurry of interest by several researchers to synthesize tMWCNTs by catalytic chemical vapor deposition (CCVD) [1,[4][5][6]. In the previous catalyst fabrication methods for t-MWCNT synthesis, a combustion process has commonly been used to obtain Fe-Mo/MgO, [1,4] Ni-Mo/MgO [5] or Co-Mo/MgO [6] catalyst materials. To prepare a homogeneous and efficient catalyst, it is desirable to fabricate well dispersed catalyst nanoparticles without agglomeration on the support materials [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, carbon materials such as carbon nanotubes (CNTs), carbon nanofibers and mechanically milled graphites have attracted attention owing to the availability of new carbon materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, most studies concerning the hydrogen storage have been carried out at high pressures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and low temperatures (80-133 K) in order to store molecular hydrogen by physisorption. It has been often reported that hydrogen storage by physisorption remains less than 4 wt% at room temperature and even high pressures [1,2].…”
Section: Introductionmentioning
confidence: 99%